Need for community-based primary prevention of coronary heart disease in Nepal - Vaidya, A (Kathmandu University Medical Journal, 2009)
doi: 10.3126/kumj.v6i4.1730 Kathmandu University Medical Journal (2008), Vol. 6, No. 4, Issue 24, 435-436